Sosialisasi Kemukjizatan Al Qur’an Terhadap Komunitas Pendengar Radio Baiturrahman Aceh Melalui Program Interaktif Al Qur’an dan Sains - Nirwana, Andri; Fitri, Ainal; Rahmadon, Rahmadon; Arfan, Fahmi; Zahari, Zahari; Sari, Fitri Meliya (IAIN Madura, 2019)
This dedication article aims to socialize the miracles of the Qur'an in the scientific field. Based on our observation that the public does not know what scientific content the Qur'an has. The findings from the results of this dedication are people with an educational background who have a good understanding of the delivery of material content, it is different from ordinary people, their impression of this program is good and requires a slow delivery strategy so that the message conveyed can be understood. This activity provides many benefits to the Radio community listeners loyal to Baiturrahman in increasing insight, literacy in understanding the miracles of the Qur'an.